The Role of Micrornas as Biomarkers in Papillomavirus- Induced Cervical Cancer - Üstündağ, Yasemin (İnönü Üniversitesi, 2026)
Despite being preventable, cervical malignancy remains a major cause of mortality among women, particularly in low-resource settings with limited screening availability. Although high-risk human papillomavirus (HPV) types 16 and 18 are the primary causative agents, malignant progression occurs in only a minority of cases, suggesting that viral presence must be supplemented by host-specific molecular, genetic, and epigenetic factors. Thus, cervical carcinogenesis is a complex multistep biological process. Recent research has identified microRNAs (miRNAs) as prominent regulators of this process, playing key roles in post-transcriptional gene modulation. These small non-coding RNA molecules govern essential functions, including cellular proliferation, apoptosis, cell cycle regulation, epithelial-mesenchymal transition (EMT), DNA damage response, and immune evasion. By binding to the 3' untranslated regions (3′-UTRs) of target mRNAs, miRNAs maintain cellular homeostasis through mRNA degradation and translational inhibition. The current literature confirms significant miRNA dysregulation in cervical cancer; a phenomenon closely linked to HPV E6 and E7 oncoproteins. While targeting tumor suppressors such as p53 and retinoblastoma protein (pRb), these viral oncoproteins simultaneously manipulate specific miRNAs, oncomiRs, or tumor-suppressive miRNAs to exacerbate malignant transformation. Notably, the dysregulation of certain miRNAs significantly impacts tumor invasion, angiogenesis, metastatic potential, and chemoradiotherapy resistance. Consequently, this study details the molecular pathways contributing to malignancy through altered miRNA expression during HPV infection and evaluates their clinical potential as non-invasive diagnostic tools, prognostic indicators, and innovative therapeutic targets for HPV-associated cancers.
Keywords: Cervical Cancer; HPV; miRNA; Biomarkers